2015
DOI: 10.1007/s12253-015-9913-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mediators of Inflammation in Cancer Development

Abstract: Epigenetic disorders such as point mutations in cellular tumor suppressor genes, DNA methylation and post-translational modifications are needed to transformation of normal cells into cancer cells. These events result in alterations in critical pathways responsible for maintaining the normal cellular homeostasis, triggering to an inflammatory response which can lead the development of cancer. The inflammatory response is a universal defense mechanism activated in response to an injury tissue, of any nature, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
168
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(172 citation statements)
references
References 61 publications
0
168
0
4
Order By: Relevance
“…Low-grade inflammation correlates with a set of chronic conditions [1,2] such as obesity [3], diabetes [3,4], cardiovascular diseases [5,6] and cancer [7,8]. This association has also been found in youth for obesity [9][10][11], central obesity [12,13], metabolic syndrome [14,15], atherosclerosis [16], and several other cardiovascular risk factors [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade inflammation correlates with a set of chronic conditions [1,2] such as obesity [3], diabetes [3,4], cardiovascular diseases [5,6] and cancer [7,8]. This association has also been found in youth for obesity [9][10][11], central obesity [12,13], metabolic syndrome [14,15], atherosclerosis [16], and several other cardiovascular risk factors [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, epidemiological studies have suggested that chronic inflammation may tend to initiate cancer through DNA damage or mutations that are affected by reactive oxygen species and some nitrogen derivatives2. According to clinical research, patients with an inflammatory bowel disease, such as Crohn’s disease or ulcerative colitis, have a high risk of suffering from colorectal cancer3.…”
mentioning
confidence: 99%
“…On the other hand, a range of inflammation mediators [cytokines, chemokines, free radicals, prostaglandins, transcription factors, microRNAs, and enzymes such as, arginase (ARG1), indoleamine 2,3-dioxygenase (IDO), cyclooxygenase and matrix metalloproteinase (MMP), nitric oxide synthase (NOS2)] are released by or reside in cancer cells and immune cells, collectively act to create a favorable microenvironment for the development of tumors. Transforming growth factor β (TGF-β) and IL-10 are the major immune suppressive cytokines secreted by tumor cells, MDSC, and TAMs while several proinflammatory cytokines (IL-1, IL-6, TNF-α) that mediate chronic inflammation in the tumor, significantly contribute to tumorigenesis and progression [27].…”
Section: Immune Cells and Mediators In Tumorsmentioning
confidence: 99%